Teaching, service and community integration as a strategy for reorienting undergraduate health training - Mendes, Tatiana de Medeiros Carvalho; Ferreira, Tainara Lorena Dos Santos; Castro, Janete Lima de; Bezerra, Héllyda de Souza; Medeiros, Aline Grimberg Pereira de; Andrade , Fábia Barbosa de (Acta Scientiarum. Health Sciences, 2022)
The teaching-service-community integration is an important strategy for achieving changes in the training of human resources in health, in order to train professionals with a profile to work in the Brazilian Unified Health System (SUS, as per its Portuguese acronym). This study analyzed how it occurs and what are the contributions of the teaching-service-community integration in the view of professors from the first to the seventh period of Medicine, Nursing and Dentistry programs at a university in northeastern Brazil. This is an exploratory and descriptive study, with a quantitative approach. Data were collected using an interview form and analyzed with the help of SPSS software. The descriptive analysis of the data, the chi-square test and the calculation of the internal consistency of the evaluation scale were used. The study had the participation of 106 professors. Results show that practices were still predominantly performed in university clinics and hospitals, 76 (71.7%). Most professors, 59 (56.7%), consider the teaching-service-community interaction very important for the quality of training and recognize its importance in strengthening SUS, 89 (85.6%). Although there was resistance on the part of some professors to follow-up students in extramural services, most of them, 94 (89.5%), consider the role of professors as essential for changing health practices, especially professors in nursing and dentistry professors that carry out extramural practices (p < 0.01). Interdisciplinary practices were performed more frequently in the first two periods of the three courses and by the nursing course (p = 0.001). In turn, multiprofessional interaction predominates in the practical classes of the nursing course and practices held outside the university domain (p < 0.01). It is evident the need to institutionalize the teaching-service-community interaction, as well as to value initiatives that streamline and make teaching more flexible in multiprofessional and interdisciplinary activities, fundamental for the amendment of training in health.